A versatile microfluidic device for high throughput production of microparticles and cell microencapsulation. Issue 12 (11th May 2017) - Akbari, Samin; Pirbodaghi, Tohid; Kamm, Roger D.; Hammond, Paula T.
Abstract : We introduce a robust microfluidic platform for production of relatively homogenous microdroplets at generation frequency of up to 3.1 MHz, about three orders of magnitude higher than the production rate of a conventional microfluidic dropmaker. Abstract : Biocompatible microparticles are valuable tools in biomedical research for applications such as drug delivery, cell transplantation therapy, and analytical assays. However, their translation into clinical research and the pharmaceutical industry has been slow due to the lack of techniques that can produce microparticles with controlled physicochemical properties at high throughput. We introduce a robust microfluidic platform for the production of relatively homogeneous microdroplets at a generation frequency of up to 3.1 MHz, which is about three orders of magnitude higher than the production rate of a conventional microfluidic drop maker. We demonstrated the successful implementation of our device for production of biocompatible microparticles with various crosslinking mechanisms and cell microencapsulation with high cell viability.